Identify The Cause and Effect of Detonation In The Main Engine - Tjahjono, Agus; Cahyadi, Tri; Indriyani, Kristin Anita; Maulana, Ilham (RSF Conference Series: Engineering and Technology, 2023)
In the process of shipping, the main engine must always be maintained in prime condition to support the smooth sailing of a ship. In the main engine, there are often oddities or things that are not common in the main engine, one of which is knocking. The purpose of this study is to identify detonation that occurs in the main engine, analyze the causes and consequences of detonation. The research method used in this research is qualitative. Sources of research data obtained from data collection techniques through observation, interviews, documentation, and data validity techniques using internal validity. The place and time of the research were conducted at MV. Tanto Hemat for one year. SWOT method to analyze various factors that can be used to optimize blasting systematically against strengths, weaknesses, opportunities, and threats. The study results identify detonation in the main engine, namely ignition delay and pre-ignition in the main engine. Factors that cause detonation in the main engine are poor fuel quality, high pressure and temperature in the engine combustion chamber, and improper combustion timing. The impact caused by detonation on the main engine is detonation will cause an increase in fuel consumption, damage to engine spare parts, and carbon buildup in the combustion chamber.